1960
DOI: 10.1063/1.1735808
|View full text |Cite
|
Sign up to set email alerts
|

Ultra-High-Speed Photographs Refuting ``Cohesion in Plasma''

Abstract: In a recent issue of this journal [M. A. Cook and W. S. McEwan, J. Appl. Phys. 29, 1612 (1958)] and in a recent book [Melvin A. Cook, The Science of High Explosives (Rheinhold Publishing Corporation, New York, 1958), 1st ed., pp. 158, 420–426], a sequence of framing camera pictures was presented, and the sequence was interpreted as evidence that, as the result of the detonation of a quantity of explosive, a plasma was ejected into the atmosphere, and that the plasma exhibited a strong cohesive force. This pape… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

1962
1962
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 4 publications
0
9
0
Order By: Relevance
“…One end of the bare explosive was connected to a detonator and the other end was attached to the circular hole. The explosively generated plasma ejected from the circular hole into the measurement region was the research object in this paper [3][4][5][6][7]. All explosives were fired by electric detonators that were initiated by a capacitive discharge unit (FD100, Yingkou Feiya Technology Co., Ltd, China).…”
Section: • • • ()mentioning
confidence: 99%
See 2 more Smart Citations
“…One end of the bare explosive was connected to a detonator and the other end was attached to the circular hole. The explosively generated plasma ejected from the circular hole into the measurement region was the research object in this paper [3][4][5][6][7]. All explosives were fired by electric detonators that were initiated by a capacitive discharge unit (FD100, Yingkou Feiya Technology Co., Ltd, China).…”
Section: • • • ()mentioning
confidence: 99%
“…A large number of charged particles are generated from a condensed explosive, which form a certain volume of weakly ionized non-ideal plasma [1,2]. This plasma is transient and time-varying and is called an explosively generated plasma [3][4][5][6]. This is an important object for studying the thermodynamic and electromagnetic effects from explosions.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The rapid heat pulse, termed "flash-across," is qualitatively analogous to the hypervelocity wave AB in figure 5, but it has been reported to propagate much faster (up to 100 km./-sec.). An increase of electrical conductivity of the solid explosive behind the shock front ifi an observed fact (10), but its quantitative consequences (71), as well as the interpretation of the photographic evidence of high electronic density phenomena sup-porting the heat-pulse theory (39), are the matter of some controversy.…”
Section: Shock-initiation Of Detonationmentioning
confidence: 99%
“…It is known that the temperature of the plasma is of the order of 1 eV depending on the test configuration [1][2][3][4][5]. It has been shown that gaseous ejecta or plasma from detonating high explosives travel at 10 km/s in cylindrical shock tubes [1,[6][7][8] and can be focused in conical shock tubes to achieve impact velocities as high as 25 km/s (this work, framing camera studies).…”
Section: Introductionmentioning
confidence: 99%